Transformation of Amoxapine by Cunninghamella elegans - Moody, Joanna D. (American Society for Microbiology, 2000)
We examined Cunninghamella elegans to determine its ability to transform amoxapine, a tricyclic antidepressant belonging to the dibenzoxazepine class of drugs. Approximately 57% of the exogenous amoxapine was metabolized to three metabolites that were isolated by high-performance liquid chromatography and were identified by nuclear magnetic resonance and mass spectrometry as 7-hydroxyamoxapine (48%), N-formyl-7-hydroxyamoxapine (31%), and N-formylamoxapine (21%). 7-Hydroxyamoxapine, a mammalian metabolite with biological activity, now can be produced in milligram quantities for toxicological evaluation.